ASSESSMENT OF THE COMPANY’S FINANCIAL CONDITION AND FACTORS AFFECTING IT - Masharipov, Masud Numondjonovich; Bekmurodov , Sardor Ro‘ziboy o‘g‘li (Educational Research in Universal Sciences, 2023)
The financial results of the enterprise are characterized by the amount of profit and the level of profitability. The greater the amount of profit and the higher the level of profitability, the more efficient the enterprise works, the more stable its financial condition is. Therefore, determining reserves to increase profit and profitability is one of the main tasks in any business field, and financial analysis is given great importance in its determination. The purpose of this scientific work is to assess the financial status of the enterprise based on financial analysis, to determine the effectiveness of the enterprise’s work, to study and analyze the factors affecting the financial status of the enterprise.